Diagnostic accuracy of loop-mediated isothermal amplification (LAMP) for detection of Leishmania DNA in buffy coat from visceral leishmaniasis patients - Khan, Md. Gulam Musawwir; Bhaskar, Khondaker Rifat Hasan; Salam, Md. Abdus; Akther, Tania; Pluschke, Gerd; Mondal, Dinesh (BioMed Central, 2012)
Background: Visceral leishmaniasis (VL) remains as one of the most neglected tropical diseases with over 60% of the world’s total VL cases occurring in the Indian subcontinent. Due to the invasive risky procedure and technical expertise required in the classical parasitological diagnosis, the goal of the VL experts has been to develop noninvasive procedure(s) applicable in the field settings. Several serological and molecular biological approaches have been developed over the last decades, but only a few are applicable in field settings that can be performed with relative ease. Recently, loop-mediated isothermal amplification (LAMP) has emerged as a novel nucleic acid amplification method for diagnosis of VL. In this study, we have evaluated the LAMP assay using buffy coat DNA samples from VL patients in Bangladesh and compared its performance with leishmania nested PCR (Ln-PCR), an established molecular method with very high diagnostic indices. Methods: Seventy five (75) parasitologically confirmed VL patients by spleen smear microcopy and 101 controls (endemic healthy controls −25, non-endemic healthy control-26, Tuberculosis-25 and other diseases-25) were enrolled in this study. LAMP assay was carried out using a set of four primers targeting L. donovani kinetoplast minicircle DNA under isothermal (62 °C) conditions in a heat block. For Ln-PCR, we used primers targeting the parasite’s small-subunit rRNA region. Results: LAMP assay was found to be positive in 68 of 75 confirmed VL cases, and revealed its diagnostic sensitivity of 90.7% (95.84-81.14, 95% CI), whereas all controls were negative by LAMP assay, indicating a specificity of 100% (100–95.43, 95% CI). The Ln-PCR yielded a sensitivity of 96% (98.96-87.97, 95% CI) and a specificity of 100% (100–95.43, 95% CI). Conclusion: High diagnostic sensitivity and excellent specificity were observed in this first report of LAMP diagnostic evaluation from Bangladesh. Considering its many fold advantages over conventional PCR and potential to be used as a simple and rapid test in the VL endemic areas of the Indian subcontinent, our findings are encouraging, but further evaluation of LAMP is needed.